1988
DOI: 10.1071/bi9880177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone Administration on Wool Growth in Merino Sheep

Abstract: The effects of daily administration of 10 mg of highly purified ovine growth hormone (GH) for a period of 4 weeks on wool growth have been measured in 12 Merino ewes fed either a calculated maintenance energy intake or 1·6 times this amount (six on each ration). Concentrations of hormones, glucose, urea, a-amino N and amino acids in the blood were monitored and faeces and urine collected for measurement of nitrogen balance.Wool growth rate decreased by 200/0 during the 4 weeks of GH treatment in sheep fed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 46 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Studies have shown that wool follicle activity and wool production are hormonally influenced. For example, Wynn et al (1988) observed that wool growth rate decreased and wool fibre diameter was reduced in Merino ewes treated with ovine growth hormone. The authors assumed that the changes in wool growth were caused by a change in the partitioning of amino acids between the muscle mass and the skin.…”
Section: Resultsmentioning
confidence: 94%
“…Studies have shown that wool follicle activity and wool production are hormonally influenced. For example, Wynn et al (1988) observed that wool growth rate decreased and wool fibre diameter was reduced in Merino ewes treated with ovine growth hormone. The authors assumed that the changes in wool growth were caused by a change in the partitioning of amino acids between the muscle mass and the skin.…”
Section: Resultsmentioning
confidence: 94%
“…The incorporation of labeled cystine, as previously used to measure the rate of wool growth (Wynn et al, 1988), was applied to the measurement of mouse vibrissa length. At 11, 16, and 21 d of age each mouse received a single, intraperitoneal injection of 0.25 µCi 35 S-L-cystine (specific activity 250 mCi per mM, Amersham) in 0.1 ml 0.9% (wt/vol) NaCl.…”
Section: Measurement Of Vibrissa Lengthmentioning
confidence: 99%
“…Oakes et al (1992) and Lobie et al (1990) found that GHR was widely distributed in skin fibroblasts, the internal and external root sheath, and dermal papillae etc. Wynn et al (1988) found GHR expression in the primary and secondary hair follicles of goats using in situ hybridisation while Mu et al (2006) also found GHR expression in sheep hair follicles. In the present study, GHR gene expression was upregulated in the higher-hairdensity group, which suggests that GHR controls hair follicle development in Rex rabbit foetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of GHR and KAP6.1 from the KAP (Keratin Associated Protein) family and downregulation of TGF-β1 from the TGF-β family have been previously associated with hair follicle development (Wynn et al, 1988;Zhang et al, Bickel et al, 2008). Additionally, the Small proline-rich protein 3 (SPRP3) has also been associated with hair follicle development (Hohl et al, 1995).…”
Section: Discussionmentioning
confidence: 99%